Scientific experiments in early childhood education: activities planned by pre-service teachers - Tovar-Gálvez, Julio César (Investigações em Ensino de Ciências, 2026)
There is evidence that teachers rarely implement scientific experiments in the early childhood education (ECE) classroom. Part of the problem lies in initial teacher education. This paper proposes alternatives to improve pre-service ECE teachers' knowledge of science teaching, based on their difficulties in planning scientific experiments. Methodologically, this is a qualitative study that inductively analyses the planning of an experiment presented by a sample of 97 pre-service ECE teachers. The results describe the activities before, during and after the planned experiment. The discussion addresses popular experiments that can lead to conceptual distortions, more adequate experiments, and considerations that can improve ECE teacher education.